Warm compress therapy's impact on labour pain in intranatal patient: A systematic review - Astuti, Rahayu; Anggraeni, Mekar Dwi; Awaludin, Sidik (Science Midwifery, 2024)
Labor and birth is a normal physiological events, a thrilling thing for prospective mothers because they will experience conditions of discomfort and fear. One of the problems in laboring women is pain that has an impact on physical and psychological. Here non-pharmacological pain management can be done, among others, with warm compresses and proven to lessen labouring mothers' suffering. The purpose of this study was to determine how warm compresses affected laboring mothers' pain. This study employed a systematic review as its research approach. Article searches are carried out using Google Scholar and Pubmed, Semantic, and Portal Garuda with the Keywords: labour pain is decreased by warm compress therapy. Original randomized controlled trials (RCTs) published between 2013 and 2023 met the inclusion requirements. There were ten randomized controlled trials in total. The main methods of employing warm compresses to lessen labor pain included the hydro collator pack, which was submerged in warm water, A warm, damp towel that saturates the contact and causes the iron to oxidize Belt with infrared. Conclusion: Warm compress therapy affects reducing pain in intranatal patients.